Desarrollo de una propuesta de mejora de la planta de tratamiento de aguas residuales para la reducción de la DQO Y DBO en la Fábrica De Chocolates Triunfo S.A. (2018)
An improvement proposal is made for the Chocolates Factory Triunfo S.A.’s wastewater treatment plant. starting with the analysis of the historical characterizations of each of the general water parameters and a diagnosis of the current state in which the wastewater treatment plant (WWTP) operates. Based on this information, the selection of the treatment to be evaluated in a laboratory scale is made by means of a selection matrix that evaluates the alternatives of coagulation-flocculation, electrocoagulation, ozonation and biological treatment based on five criteria (percentage of removal, estimated costs of supplies and equipment, required area, availability of materials and equipment for laboratory-scale evaluation). The coagulation-flocculation selection was made as the best alternative and then the experimental design was carried out in which the coagulant, the operating conditions and the coagulant and flocculant dosage were determined. Subsequent to this, two characterizations were made to the residual water in external laboratories, where the parameters of COD and BOD were measured with and without the application of physicochemical treatment. Finally, the conceptual design of the improvement proposal is elaborated starting from the data collected from the experimental development and a financial analysis of the proposal is made using the benefit / cost ratio and the net present value (NPV) as project feasibility measures.